Nisab Zakat Profi E-Sport Perspective Qiyas - Livia Nanda Chairunnisa Nasution; Abd Rahman Harahap (Journal Equity of Law and Governance, 2024)
One of the uses of technology in the video game industry has led to a new reality: playing video games can now become a profession with significant income. E-Sports (Electronic Sports) is a form of competitive video gaming that demands high skill and teamwork to achieve victory. This profession has grown in popularity as its income often far exceeds the regional minimum wage in various cities. This situation raises questions about the obligation of zakat for e-sports players, considering that in Islam, zakat is required for professions whose income reaches the nisab or minimum threshold. Zakat plays a crucial role in promoting wealth distribution and community welfare. However, applying zakat to modern professions such as e-sports requires adjustments in terms of nisab, rate, and payment timing, which can be determined through the method of qiyas (analogy). This study aims to examine the concept of the nisab for professional zakat in e-sports from a qiyas perspective. The research uses a normative approach with a conceptual approach, where data analysis is conducted through literature review by studying relevant theories from related literature. The analysis shows that income from the e-sports profession is subject to zakat, using the analogy of gold zakat, with a nisab value of 85 grams of gold and a zakat rate of 2.5%.